Analisis Sistem Tanggap Darurat Kebakaran di Lapangan Penumpukan Terminal Petikemas PT. Berlian Jasa Terminal Indonesia Tanjung Perak Surabaya - Muhammad Rizal Ramadhani; Muhammad Kemal Fahrezi; Moch. Luqman Ashari (Journal of Student Research, 2023)
Berlian Jasa Terminal Indonesia (BJTI) is a terminal port that serves container loading and unloading services at the port. One of the hazards that threaten the loading and unloading industry is the danger of fire. Fires can cause a lot of material and non-material losses. Efforts that can be made to minimize the danger and impact of fires are the implementation of an efficient and optimal emergency response system in accordance with applicable regulations and standards. This study aims to analyze the implementation of the emergency response system in an effort to prevent and control fires in the PT. Berlian Terminal Services Indonesia. This research is a descriptive qualitative research, with primary data sourced from direct observation and interviews, while secondary data obtained through a literature study of company documents. This research will explain how the implementation of the fire emergency response system in PT. Berlian Terminal Services Indonesia. The result of this research is that it can be concluded that PT. Berlian Jasa Terminal Indonesia has implemented a fire emergency response system in accordance with applicable regulations and standards, but there are still things that need to be optimized, such as the implementation of APAR inspections that are late in their implementation and the lack of intensity in fire emergency response simulations.